The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1136/ard.2009.112474
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rates of joint surgery among patients with rheumatoid arthritis in California, 1983-2007

Abstract: Objectives Treatment of patients with rheumatoid arthritis (RA) has improved markedly over the past 25 years. We investigated if rates of joint surgery, a long-term consequence of poorly-controlled RA, have changed over this period. Methods In this population-based, serial cross-sectional study of patients aged ≥ 40 years with RA in California, we examined trends in annual rates of total knee arthroplasty, total hip arthroplasty, total ankle arthroplasty or arthrodesis, and total wrist arthroplasty or arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 11 publications
7
73
1
3
Order By: Relevance
“…In a sense, total joint replacement represents the failure of medical treatment to control RA adequately, and the incidence of total joint replacement is a measure of disease progression and the ineffectiveness of treatment (14). The incidence of total joint replacement decreases with time, likely due to advances in RA treatment with MTX and biologic DMARDs (23)(24)(25)(26)(27). A previous study suggested that in order to inhibit the need for total joint replacement in patients treated with TNF inhibitors, it is important to maintain tight control over RA activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a sense, total joint replacement represents the failure of medical treatment to control RA adequately, and the incidence of total joint replacement is a measure of disease progression and the ineffectiveness of treatment (14). The incidence of total joint replacement decreases with time, likely due to advances in RA treatment with MTX and biologic DMARDs (23)(24)(25)(26)(27). A previous study suggested that in order to inhibit the need for total joint replacement in patients treated with TNF inhibitors, it is important to maintain tight control over RA activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a reduction in the rates of orthopaedic joint arthroplasty for rheumatoid patients [8,11,12,18,23] as well as a recent study that highlights the apparent decline of hand surgery for patients with RA [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Californian adults over two decades Louie et al 2010 [13] noted that the demand for knee arthroplasty decreased in younger patients, and paralleled the general population requirements in older patients. The introduction of the use of methotrexate in the 1970s, and more recently the use of Tumour Necrosis Factor α has been attributed to milder forms of the disease and the slowing of radiographic deterioration [14].…”
Section: Incidence / Prevalencementioning
confidence: 99%
“…Without appropriate pharmacological treatment or surgical intervention it can lead to profound disability and pain. The evolution of disease modifying anti-rheumatoid drugs (DMARDs) has had a significant effect on the number of patients requiring surgery [13].…”
Section: Aetiologymentioning
confidence: 99%